Generation of 629 nm Pulsed Laser Using an Optical Parametric Amplifier - Nafil, Rabeah Q.; Jawad, Hussein A. (Iraqi Journal of Laser, 2007)
The main purpose of this work is the construction of an optical parametric amplifier (OPA) to generate a 629 nm pulsed laser. KTP nonlinear crystals were used for both parametric oscillation and amplification. A singly resonant parametric oscillator (OPO) is constructed to generate a signal of 1.54 μm and idler of 3.4 μm when the OPO system is pumped by 1.064 μm Q – switched Nd: YAG laser. The signal was then mixed with the pumping beam in OPA system to form the wanted wavelength. The obtained optical conversion efficiency was 60%.